Implementasi Metode Yanbu’a Dalam Meningkatkan Kefasihan Membaca Al-Qur’an Pada santri BTA Pondok Pesantren Ath-Thohiriyyah Purwokerto Ika Mustika Ratri, Imam Hidayat - Mustika Ratri, Ika; Hidayat, Imam (Jurnal Pendidikan Agama Islam, 2025)
This research contains the application of the Yanbu’a Method in improving fluency in reading the Qur'an among BTA students at Ath-Thohiriyyah Islamic Boarding School in Purwokerto. The purpose of this research is (1) to analyze the implementation of the Yanbu’a Method in improving the fluency of reading the Qur'an among BTA students at Ath-Thohiriyyah Islamic Boarding School in Purwokerto. (2) To analyze the factors that support and hinder the implementation of the Yanbu’a Method in improving the fluency of reading the Qur'an among BTA students at Pondok Pesantren Ath-Thohiriyyah Purwokerto. This research is a qualitative study of a descriptive nature. The data collection techniques used are observation, interviews, and documentation. The data sources in this study are the ustadzah teaching the Yanbu’a Method and the stage 1 BTA students. The results of this study indicate that the implementation of the Yanbu’a Method at Pondok Pesantren Ath-Thohiriyyah is carried out systematically, starting from the presentation of material, Musyafahah, Ardul Qiraah, repetition, and evaluation. This method can facilitate students in understanding tajwid so that they can read the Qur'an well and correctly. Supporting factors in the implementation of this method include the active role of teachers in conducting lessons, concise and systematic materials, and the teachers' background in attending LMY training before applying the Yanbu’a Method. The inhibiting factors include the lack of awareness and willingness among students to read the Qur'an fluently and the varying abilities of students in understanding the material.